2007
DOI: 10.1158/1541-7786.mcr-07-0098
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Pre-S2 Mutant Surface Antigen Induces Degradation of Cyclin-Dependent Kinase Inhibitor p27Kip1 through c-Jun Activation Domain-Binding Protein 1

Abstract: The hepatitis B virus (HBV) large surface antigen (LHBS) mutant with deletion at the pre-S 2 region accumulates in endoplasmic reticulum (ER) and is associated with HBV-induced hepatocellular carcinogenesis. In this study, we found that the pre-S 2 LHBS mutant directly interacts with the Jun activation domain -binding protein 1 (JAB1). Association of pre-S 2 LHBS with JAB1 dissociated JAB1 from the JAB1/IRE1 complex in ER. The free (active) JAB1 then translocated into cell nuclei and rendered the Cdk inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 36 publications
3
71
0
Order By: Relevance
“…Although interactions with components of the CRLs have been described previously for DNA and RNA viruses, only few examples of interactions with the CSN complex have been reported, all limited to animal viruses (Mahalingam et al, 1998;Oh et al, 2006;Tanaka et al, 2006;Hsieh et al, 2007). Even though, as for C2-CSN5, those interactions seem to play a role during virus infection (Oh et al, 2006;Tanaka et al, 2006;Hsieh et al, 2007), the mechanisms proposed point to a redirection of proteosomal degradation rather than to an effect on the derubylating activity of the CSN complex itself.…”
Section: Jasmonate Treatment Reduces the Susceptibility To Geminivirumentioning
confidence: 96%
See 1 more Smart Citation
“…Although interactions with components of the CRLs have been described previously for DNA and RNA viruses, only few examples of interactions with the CSN complex have been reported, all limited to animal viruses (Mahalingam et al, 1998;Oh et al, 2006;Tanaka et al, 2006;Hsieh et al, 2007). Even though, as for C2-CSN5, those interactions seem to play a role during virus infection (Oh et al, 2006;Tanaka et al, 2006;Hsieh et al, 2007), the mechanisms proposed point to a redirection of proteosomal degradation rather than to an effect on the derubylating activity of the CSN complex itself.…”
Section: Jasmonate Treatment Reduces the Susceptibility To Geminivirumentioning
confidence: 96%
“…Even though, as for C2-CSN5, those interactions seem to play a role during virus infection (Oh et al, 2006;Tanaka et al, 2006;Hsieh et al, 2007), the mechanisms proposed point to a redirection of proteosomal degradation rather than to an effect on the derubylating activity of the CSN complex itself.…”
Section: Jasmonate Treatment Reduces the Susceptibility To Geminivirumentioning
confidence: 99%
“…The preS mutated proteins accumulating in the ER can trigger c-Raf-1/Erk2 signaling, which results in AP1 and NFκB activation, enhanced proliferative activity of hepatocytes and an increased incidence of liver tumors in transgenics [52] . Pre-S2 mutated proteins also have non-ER related functions such as interacting with Jun activation domain binding protein 1, which results in cyclindependent kinase inhibitor p27 degradation and cell cycle progression [53] . Oxidative stress must be involved to some degree in HBVrelated hepatocarcinogenesis, possibly via HBx and pre-S-related functions.…”
Section: Mechanisms Of Hbv-related Hcc and Oxidative Stress Involvementmentioning
confidence: 99%
“…It also induces the overexpression of cell cycle regulator cyclin A and causes cell cycle progression in the presence of DNA lesions (13). We recently (14) found that ⌬2 LHBS directly interacts with c-Jun activation domain-binding protein 1 (JAB1) and subsequently causes hyperphosphorylation of the tumor suppressor retinoblastoma and, consequently, G 1 -to S-phase cell cycle progression.…”
Section: Hronic Hepatitis B Virus (Hbv) Infection Is the Most Impormentioning
confidence: 99%
“…It also induces the overexpression of cell cycle regulator cyclin A and causes cell cycle progression in the presence of DNA lesions (13). We recently (14) found that ⌬2 LHBS directly interacts with c-Jun activation domain-binding protein 1 (JAB1) and subsequently causes hyperphosphorylation of the tumor suppressor retinoblastoma and, consequently, G 1 -to S-phase cell cycle progression.JAB1 is a key subunit of the COP9 signalosome (CSN) and acts as a multifunctional protein associated with the signaling pathway, cell cycle regulation, and development. JAB1 is oncogenic because it promotes cell proliferation by increasing transcription of activator protein 1 (AP-1) and stimulates cell cycle progression by increasing the degradation of the cyclin-dependent kinase inhibitor p27 Kip1 (15,16).…”
mentioning
confidence: 99%